2019
DOI: 10.1111/nph.15865
|View full text |Cite
|
Sign up to set email alerts
|

Invasive annuals respond more negatively to drought than native species

Abstract: Summary In his foundational list of ‘ideal weed’ characteristics, Baker (1965) proposed that weedy plants maximize reproductive output under high resource availability. Since then, the idea that invasive plant species are more responsive to fluctuating resources compared with native or noninvasive species has gained considerable traction, although few studies extend this hypothesis to include reproductive output. We revisit Baker's hypothesis in the context of invasion and drought in California grasslands, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
57
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 51 publications
4
57
1
Order By: Relevance
“…Changes in precipitation will certainly affect invasive populations in addition to their co‐occurring natives. Various studies have found these grasses to increase under high resource conditions and decrease under low‐resource conditions (Prevéy and Seastedt 2014, Copeland et al 2016, Valliere et al 2019, Puritty et al 2019). Our study did not find any effects of either watering treatment on grass cover, possibly because of its short duration and moderate intensity of watering treatments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Changes in precipitation will certainly affect invasive populations in addition to their co‐occurring natives. Various studies have found these grasses to increase under high resource conditions and decrease under low‐resource conditions (Prevéy and Seastedt 2014, Copeland et al 2016, Valliere et al 2019, Puritty et al 2019). Our study did not find any effects of either watering treatment on grass cover, possibly because of its short duration and moderate intensity of watering treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Our study did not find any effects of either watering treatment on grass cover, possibly because of its short duration and moderate intensity of watering treatments. Invasive annual grasses have been shown to be competitively superior over natives regardless of water availability (Leishman et al 2007, van Kleunen et al 2010, Valliere et al 2019), and to maintain their dominance despite observed declines under drought (Puritty et al 2019, Valliere et al 2019, Winkler et al 2019). While unexpected, this aspect of our study allowed us to examine the relative vulnerabilities of acquisitive and conservative native species without the additional influence of treatment‐driven variation in invasive grass abundance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of seed traits, seed quality and germination, to a larger extent, determine the recruitment of seedlings and dynamics of plant populations (Fenner and Thompson, 2006;Harper, 2010). Similarly, for plant invaders, seed quality and germination largely influence their success, and ultimately shape their capacity to exclude native plants (Valliere et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…An abundant literature shows that seed quality and germination are unavoidably influenced by a wide range of ecological factors (Harper and Benton, 1966;Baskin and Baskin, 1998;Guillemin and Chauvel, 2011;Valliere et al, 2019;Wang and He, 2019). One of these, air temperature has long been recognized as an important factor influencing seed quality and germination (Baker, 1965;Baskin and Baskin, 1998;Fenner and Thompson, 2006).…”
Section: Introductionmentioning
confidence: 99%